2009
DOI: 10.1111/j.1365-2133.2009.09296.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Flightless I, an actin-remodelling protein, improves burn injury repair via modulation of transforming growth factor (TGF)-β1 and TGF-β3

Abstract: Strategies aimed at reducing Flii expression, for example using neutralizing antibodies, may lead to improved burn outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 27 publications
2
53
1
Order By: Relevance
“…Diabetic wounds treated with FnAb showed accelerated wound closure with a 1.9-fold decrease in average wound size observed in day 3 and day 7 WT FnAb-treated diabetic wounds. Similar effects have been reported in previous studies where FnAb improved the rate of incisional [17], excisional [20] and burn wound repair [19]. Dose-dependent effects of FnAb on cellular proliferation have also previously been demonstrated [20] and the addition of FnAb to human chronic wound fluids can reduce their inhibitory effect on cell proliferation in vitro [18].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Diabetic wounds treated with FnAb showed accelerated wound closure with a 1.9-fold decrease in average wound size observed in day 3 and day 7 WT FnAb-treated diabetic wounds. Similar effects have been reported in previous studies where FnAb improved the rate of incisional [17], excisional [20] and burn wound repair [19]. Dose-dependent effects of FnAb on cellular proliferation have also previously been demonstrated [20] and the addition of FnAb to human chronic wound fluids can reduce their inhibitory effect on cell proliferation in vitro [18].…”
Section: Discussionsupporting
confidence: 68%
“…alcohol for 1 min each. Sections were brought to water, rinsed in ×1 PBS and placed into 250 ml target retrieval solution as described previously [19]. Primary antibodies (1:100) were applied and incubated overnight at 4°C.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Flii is upregulated in tissue in response to injury in mice and we now show fibroblasts increase secretion of Flii in response to wounding (Adams et al, 2009;Cowin et al, 2007). The upregulation of Flii in response to injury seems counterproductive since increasing the levels of Flii leads to reduced cell migration, impaired healing and increased scar formation.…”
Section: Discussionmentioning
confidence: 93%
“…1A,B). We have previously shown that Flii is upregulated in mouse skin wound tissue in response to injury (Adams et al, 2009;Cowin et al, 2007). Since Flii levels increase in the wounds of mice, scratch wounds were created in a confluent layer of NIH3T3 fibroblasts to determine whether scratch wounding these cells could alter Flii secretion.…”
Section: Flii Secretion Is Both Constitutive and Regulatedmentioning
confidence: 99%